2018
DOI: 10.1080/15487733.2018.1541682
|View full text |Cite
|
Sign up to set email alerts
|

The Anthropocene Working Group and its (inter-)disciplinarity

Abstract: This article investigates the internal dynamics of the Anthropocene Working Group (AWG), an expert body tasked with evaluating the stratigraphic case of the Anthropocene. The investigation focuses on the role of interdisciplinarity and disciplinarity in the AWG. The article draws on surveys and interviews with AWG members to characterize interdisciplinary collaboration in the AWG and discusses the relationship of the AWG to the stratigraphic community. The results reveal that the exchanges between disciplines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Since forms of knowledge have been organised into disciplinary fields have the potential and possibility of crossing boundaries been apparent and utilised to advance knowledge (Renn, 2020; Schaffer, 2013). However, continually interdisciplinarity appears as a remedy for the many scientific and environmental challenges of the present, most prominently demonstrated recently through action and research coalescing around the United Nations Sustainable Development Goals (Keynejad et al., 2021) and the Anthropocene, both practically (Lundershausen, 2018) and theoretically (Renn, 2020).…”
Section: Interdisciplinarity and The ‘Environment’ Todaymentioning
confidence: 99%
“…Since forms of knowledge have been organised into disciplinary fields have the potential and possibility of crossing boundaries been apparent and utilised to advance knowledge (Renn, 2020; Schaffer, 2013). However, continually interdisciplinarity appears as a remedy for the many scientific and environmental challenges of the present, most prominently demonstrated recently through action and research coalescing around the United Nations Sustainable Development Goals (Keynejad et al., 2021) and the Anthropocene, both practically (Lundershausen, 2018) and theoretically (Renn, 2020).…”
Section: Interdisciplinarity and The ‘Environment’ Todaymentioning
confidence: 99%
“…Ruddiman 2003Ruddiman , 2013Lane 2015). This situation hardly changed after May 2019, when the Anthropocene Working Group decided by majority vote (29 members in favour, four members against) that the Anthropocene should be treated as a formal chrono-stratigraphic unit defined by a Global Boundary Stratotype Section and Point (GSSP) (Ogg 2004;Lundershausen 2018). Evidently, the conversation about the Anthropocene has moved, as Williams claimed happens with all keywords, beyond the range of 'proper meaning', and the multiplicity of meanings attached to the Anthropocene is bound up with the problems the word is meant to discuss.…”
Section: Anthropocene: a New Keywordmentioning
confidence: 99%
“…It seems that integrating disciplines is a way to reach complexity in interpreting reality. However, Lundershausen (2018) empirically demonstrated that scientific groups have limitations to achieving such integration. Moreover, Woiwode and Froese (2020) identify that the peer-review process for publishing favour monodisciplinary research.…”
Section: Introductionmentioning
confidence: 99%